2004
DOI: 10.1111/j.1365-2621.2004.tb13615.x
|View full text |Cite
|
Sign up to set email alerts
|

Fat Migration in Chocolate: Diffusion or Capillary Flow in a Particulate Solid?—A Hypothesis Paper

Abstract: The exact mechanism of fat and oil migration in chocolate and chocolate coatings is still unknown. Nevertheless, the so-called "diffusion equation" derived from Fick's 2nd law has been extensively used to model the phenomenon, giving the impression that molecular diffusion is the single transport mechanism. We propose that chocolate may be microstructurally regarded as a particulate medium formed by an assembly of fat-coated particles (for example, cocoa solids, sugars crystals, and milk powder). Within this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
124
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 38 publications
(27 reference statements)
2
124
1
Order By: Relevance
“…In previous studies, differences in L* (38.3-43.5) and C* (11.0-14.4) were found to vary with the process conditions and storage (Aguilera et al 2004;Mexis et al 2010). In this study, chroma values varied within narrow ranges, such as 15.0±0.65-15.5±0.81 (Table 3); however, statistically significant variations were determined between the sample groups (P <0.01).…”
Section: Colourcontrasting
confidence: 42%
See 2 more Smart Citations
“…In previous studies, differences in L* (38.3-43.5) and C* (11.0-14.4) were found to vary with the process conditions and storage (Aguilera et al 2004;Mexis et al 2010). In this study, chroma values varied within narrow ranges, such as 15.0±0.65-15.5±0.81 (Table 3); however, statistically significant variations were determined between the sample groups (P <0.01).…”
Section: Colourcontrasting
confidence: 42%
“…Relevant information related to colour has be acquired from modern technologies such as computer vision and calibrated colour imaging analysis according to the HunterLab and CIELab models (Afoakwa et al 2008;Briones and Aguilera 2005;Jahns et al 2001;Hatcher et al 2004;Lawless and Heymann 1998). Colour changes are likely to be specific to each chocolate sample (Aguilera et al 2004). In previous studies, differences in colour parameters were found to vary with the particle size distribution, packaging conditions and storage (Aguilera et al 2004;Mexis et al 2010).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…These definitions recognizes the importance of the three dimensional microstructure of food, stating that the mass transport of water is a more complex phenomena than in a non-porous material (Datta, 2007a). Starting from this idea, capillary forces flow must be considered as one of the most important mass transfer mechanism during drying (Datta, 2007a), rehydration (Saguy et al, 2005) as well as during frying, and fat migration in chocolate (Aguilera et al, 2004). As known, capillary forces are responsible to the attraction among liquid molecules and between them and the solid matrix.…”
Section: Capillary Flowmentioning
confidence: 99%
“…So, capillary force are among the reasons of: a. the water transport from a region with more water to a region with less one due to the differences in capillary force; b. the difficulty to remove water from vegetable structure. Historically, Lucas-Washburn equation it is recognized as best equation to model capillary rise into a small pores (Aguilera et al, 2004). The equation shows that the pressure inside a cylindrical capillary is balanced by viscous drag and gravity (Lucas, 1912;Washburn, 1921;Krotov and Rusanov, 1999).…”
Section: Capillary Flowmentioning
confidence: 99%